Literatura infantil dos kits de literatura afro-brasileira da Prefeitura de Belo Horizonte (MG): um currículo para ressignificação das relações étnico-raciais? - Daniela Amaral Silva Freitas (2014)
Provocative, seductive, fun, creative, amazing: these are some of the adjectives used to refer to children's stories. These stories aimed at children, however, are not only charming and fun, they also produce meanings about the world and the things of the world; teach about race /ethnicity and gender; establishing standards and govern behavior. Teach ways of being, to act, to think, to want, to look at themselves and each other. Jostle for space with discourses from the most diverse spheres (family, school, religious, political ...) for the production of knowledge and subjects. These assumptions were of great importance to the research conducted for this thesis aims to examine the books of children's literature that make up kits african-brazilian literature organized by the Municipality of Belo Horizonte and distributed to all municipal schools as cultural artifacts involved in producing educated for the redefinition of ethnic and race relations subjects. This is because such kits are part of a public policy to meet the Act No. 10.639/03 and 11.645/08 paragraph which make it compulsory to african-brazilian teaching of African history and culture, and indigenous in elementary and secondary education in Brazilian schools. Inspired by cultural studies, post-colonial studies by and the post-critical curriculum studies and using theoretical and methodological tools drawn from these studies and especially the work of Michel Foucault, this thesis investigates the books of children's literature, which are part of kits of african-brazilian literature at PBH, to analyze how the blacks and indigenous are represented in the narratives and illustrations. This thesis therefore investigates the meanings disclosed about these subjects and discursive effects of these representations and meanings. The general argument of the thesis is that the books of children's literature that make up the kits of PBH constitute a curriculum that is part of the cultural struggles for change of meanings and reconfigurations of the relations of power-knowledge, to compete for place in order discourse, knowledge and subjects before silenced and denied, contributing to promote education and a redefinition of ethnic-racial relations. In this sense, the ways / as black / as and / indigenous are presented / in the investigated material are analyzed as strategies of power that senses vie with other discourses, published in other spaces and artifacts on these subjects. The books of children's literature investigated thereby seeking to regulate and govern its readership in other ways to deal with the ethnic-racial relations. Thus, it is observed in the material examined a new knowledge network be woven, in which blacks and the indigenous are produced by more plural discourses in which positive features are being main in its composition and distribution.